Abundant immunoglobulin (Ig)G4‐positive plasma cells in interstitial pneumonia without extrathoracic lesions of IgG4‐related disease: is this finding specific to IgG4‐related lung disease?. Issue 2 (29th September 2016) - Ikeda, Satoshi; Sekine, Akimasa; Baba, Tomohisa; Okudela, Koji; Iwasawa, Tae; Sakai, Fumikazu; Notohara, Kenji; Ohashi, Kenichi; Takemura, Tamiko; Ogura, Takashi
Abstract : Aims: There have been few reports on immunoglobulin‐G4 (IgG4)‐related interstitial pneumonia (IP), and its clinical features remain unclear. The objective of this study was to assess whether IP with marked IgG4‐positive plasma cell infiltration without extrathoracic lesions of IgG4‐related disease (RD) should be diagnosed as a subtype of IgG4‐RD or a separate entity. Methods and results: All consecutive patients with surgical lung biopsy‐proven idiopathic IP with an IgG4/IgG‐positive cell ratio of >40% and >50 IgG4 + plasma cells in a high‐power field without extrathoracic lesions of IgG4‐RD were reviewed retrospectively. Five patients were enrolled into this study. All patients were male with a history of smoking. Four patients met the comprehensive diagnostic criteria for IgG4‐RD. The remaining patient lacked data related to the serum IgG4 level. Histologically, a non‐specific IP pattern was observed in all patients. The key morphological features of IgG4‐RD, such as storiform fibrosis and obliterative phlebitis with lymphoplasmacytic infiltration in a loose background texture, were absent in every patient. In contrast, venule obstruction by densely packed lymphoplasmacytic infiltration was observed in two patients. Marked scarring and remodelling of the lung were also noted, which is not seen typically in IgG4‐RD. A favourable response to corticosteroid monotherapy was observed in all patients; however, two patients developed lung cancer during the course of observation. Conclusions: IP with marked IgG4‐positive plasma cell infiltration without extrathoracic lesions of IgG4‐RD had different pathological features from those of IgG4‐RD, and it is appropriate to regard this as a separate entity.